Minat Gen Z Muslim Berdonasi Melalui Digital Payment di Jabodetabek - Mutiara Solihat; Nurizal Ismail (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Perceived Usefulness (PU), Perceived Ease of Use (PEU), and Intention to Use (ITU) on Behavioral Intention (BI) to use digital payment platforms for donation purposes among Gen Z Muslims in the Jabodetabek area. A quantitative approach was employed using the Structural Equation Modeling (SEM) method with the SmartPLS software. A total of 119 respondents were selected using purposive sampling techniques. The results show that perceived usefulness has a positive and significant effect on the intention to use digital payment platforms for donation. However, perceived ease of use and intention to continue using the platform do not have a significant impact on usage intention. These findings indicate that the perceived benefits such as efficiency, speed, and ease of access to donation features are the main factors influencing Gen Z Muslims’ intention to donate digitally. The R-square value of 0.449 indicates that the model has moderate predictive power. This study suggests that digital payment providers should strengthen the perceived usefulness of their applications and promote digital donation services through targeted education and awareness campaigns, especially among the younger Muslim generation.